2013
DOI: 10.1111/j.1467-9817.2013.01556.x
|View full text |Cite
|
Sign up to set email alerts
|

A validation of parafoveal semantic information extraction in reading Chinese

Abstract: Parafoveal semantic processing has recently been well documented in reading Chinese sentences, presumably because of language‐specific features. However, because of a large variation of fixation landing positions on pretarget words, some preview words actually were located in foveal vision when readers' eyes landed close to the end of the pretarget words. None of the previous studies has completely ruled out a possibility that the semantic preview effects might mainly arise from these foveally processed previe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 43 publications
3
24
0
Order By: Relevance
“…They found negative priming from strategic expectation when the interval between prime and mask was longer (234 ms). The present results can also serve as an example to support a view by Yan, Risse, Zhou, and Kliegl (2012) and Zhou, Kliegl, and Yan (2013), who argued that when the prime is processed briefly, the semantic prime-target related representation of the target word is preactivated, leading to facilitatory effects. If the prime is processed for a relatively long time, however, nonoverlapping semantic representations start to cancel the facilitatory effects, presumably even turning a facilitatory effect into an inhibitory effect.…”
Section: Negative Priming With the Isi Between Prime And Masksupporting
confidence: 72%
“…They found negative priming from strategic expectation when the interval between prime and mask was longer (234 ms). The present results can also serve as an example to support a view by Yan, Risse, Zhou, and Kliegl (2012) and Zhou, Kliegl, and Yan (2013), who argued that when the prime is processed briefly, the semantic prime-target related representation of the target word is preactivated, leading to facilitatory effects. If the prime is processed for a relatively long time, however, nonoverlapping semantic representations start to cancel the facilitatory effects, presumably even turning a facilitatory effect into an inhibitory effect.…”
Section: Negative Priming With the Isi Between Prime And Masksupporting
confidence: 72%
“…Furthermore, semantic activations can feed back to the corresponding phonological and orthographical representations. This claim is further supported by eye movement findings: Yan et al (2009) reported a stronger semantic than a phonological parafoveal preview effect, and parafoveal semantic information is obtained very early (Yan, Risse, Zhou, & Kliegl, 2012;Zhou, Kliegl, & Yan, 2013); reliable phonological effects required both long preview durations and the high parafoveal processing efficiency afforded by highfrequency pretarget words (Tsai et al, 2012).…”
supporting
confidence: 55%
“…To investigate whether visual limitation may constrain the parafoveal-on-foveal effects, we divided trials into two groups according to landing positions on the pre-target word (Inhoff, Radach, Starr, & Greenberg, 2000; Zhou, Kliegl, & Yan, 2013). In one group of trials (57% of trials), first-fixations were located on the first characters of the 2-character pre-target words, and in the other group (43% of trials), the fixations were located on the second characters.…”
Section: Resultsmentioning
confidence: 99%